ANALISIS KREATIVITAS SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI PERBEDAAN GENDER - Sikrayati Sikrayati; Wahyuddin Wahyuddin; Andi Quraisy (INSPIRAMATIKA, 2022)
This study aims to identify and describe students' creativity in solving mathematical problems in terms of gender differences. The type of research used is qualitative research with a descriptive approach. The research subjects consisted of 6 people, namely 3 male students and 3 female students, each representing the high, medium, and low categories. The instrument used in the form of a student creativity test, totaling 3 questions that have met the validity test and to further explore information about students' creative abilities, interviews were conducted. The data analysis techniques used are data collection through creativity ability tests and interviews, data reduction, data presentation, data verification and drawing conclusions. The results showed that the description of the creativity ability of male subjects in solving mathematical problems based on categories were (1) subjects with high categories were able to meet 2 indicators of creativity including fluency and flexibility, (2) subjects with medium categories were able to meet 1 indicator of creativity, namely fluency, (3) subjects with low categories are able to meet 1 indicator of creativity, namely fluency. The description of the creative ability of female subjects in solving mathematical problems based on categories is (1) subjects with high categories are able to meet creativity indicators which include fluency, flexibility and novelty, (2) subjects with moderate categories are able to meet creativity indicators which include fluency and flexibility, (3 ) subject with low category is able to fulfill 1 indicator of creativity, namely fluency indicator.